INVERTIR EN BOLSA: EXPECTATIVAS, VOLATILIDAD Y GANANCIAS - Mauricio Pachas, Pablo (2007)
This article expresses the importance and lucrative alternative for the investors in the Stock Exchange of Lima. In the last five years, the average of profitability per year has overcome the 0% until being ended up transforming into the 2006 in the most profitable Stock Exchange in the world. In that sense the marked volatility for the influence of the external market that produces changes marked in the rates of the main actions that they quote in the international market, in that context he/she should understand each other to this market as investments of long term and that non highpriority resources should be dedicated for the investor.